Persistent anosmia and olfactory bulb atrophy after mulga (Pseudechis australis) snakebite. (July 2016) - Sethi, Moksh; Cook, Mark; Winkel, Kenneth D.
Highlights: Loss of sense of smell is an intriguing yet under-recognised snakebite complication. We report olfactory testing and imaging in a snakebite patient with persistent anosmia. Formal olfactory testing indicated severe hyposmia compared to matched controls. MRI demonstrated significantly reduced volume of both olfactory bulbs. This case demonstrates severe hyposmia complicating untreated 'mild' mulga snakebite. Abstract: Loss of sense of smell is an intriguing yet under-recognised complication of snakebite. We report olfactory function testing and neuroimaging of the olfactory bulbs in a 30-year-old man with anosmia persisting for more than 1 year after mulga ( Pseudechis australis ) snakebite. This problem was first noted by the patient 1 week after being definitely bitten in Queensland, Australia. He had then presented to a regional hospital where his envenomation was considered mild enough to not warrant antivenom administration. A week later the patient noted a reduction of sense of smell, which progressed to complete inability to smell over the ensuing weeks. On clinical review the patient's neurologic and rhinologic examination did not reveal any structural cause for anosmia. Formal olfactory testing was performed using ''sniffin' sticks" and the patient scored 17 on this test, indicating severe hyposmia (functional anosmia <16.5, normal score >30.3 for men aged 16–35 years). MRI of the brain showed no abnormalities. The olfactory bulb volumes were then measured on a volumetric T2-weighted MRI that demonstrated significantly reduced volume of both bulbs, with the right 34.86 mm 3 and left 36.25 mm 3 (normal volume ⩾58 mm 3, 10th centile). The current patient represents a rare instance of a definite, untreated, elapid (mulga snake) envenomation with an intriguing disjunction between the mildness of the systemic features and the severity of the olfactory lesion. It is also unclear if early antivenom use attenuates this condition, and due to the delayed manifestation of the symptoms, awareness of this phenomenon may be lacking amongst physicians.